Endometrial thickness in the prediction of neonatal adverse outcomes in frozen cycles for singleton pregnancies. Issue 3 (September 2021) - Hu, Kai-Lun; Kawai, Andrew; Hunt, Sarah; Li, Wentao; Li, Xiaohong; Zhang, Runjv; Hu, Yanjun; Gao, Huijuan; Zhu, Yimin; Xing, Lanfeng; Mol, Ben W.; Zhang, Dan; et al.
Abstract: Research question: Does endometrial thickness (EMT) predict adverse neonatal outcomes in singleton pregnancies after in vitro fertilization (IVF) or intracytoplasmic sperm injection (ICSI) frozen embryo transfer (FET)? Design: This retrospective study involved 13, 383 women undergoing IVF/ICSI FET cycles between January 2010 and December 2018 in Women's Hospital of Zhejiang University. The primary outcome was preterm delivery (PTD). The secondary outcomes were small for gestational age (SGA), large for gestational age (LGA) and low birthweight (LBW). Results: A total of 13, 383 FET cycles resulting in 5220 singleton live births and 8163 failed cycles were included. Multiple spline regression visualization showed an increasing risk of PTD and LBW for a thin EMT. By comparing multiple cut-off points using area under the curve, a cut-off point of 8 mm was identified, which was used to categorize EMT. A reference point of EMT greater than 8 mm was used; after adjusting for covariates, individuals with EMT less than 8 mm had an adjusted odds ratio of 1.75 (95% CI 1.30 to 2.34) for PTD, 1.57 (95% CI 1.09 to 2.26) for LBW, 0.97 (95% CI 0.63 to 1.50) for SGA and 1.04 (95% CI 0.79 to 1.37) for LGA. Additional analyses showed similar increasing risk with a thin endometrium for both PTD with and without caesarean section, and PTD with low and normal birthweight percentiles. Conclusion: A clinical cut-off point of 8 mm has been identified, below which risk of PTD and LBW increases in women undergoing IVF/ICSI.